Exploring the present state of South African education: Challenges and recommendations - Maddock, L.; Maroun, W. (South African Journal of Higher Education, 2018)
In the light of widespread concern about, and continual questioning of, South African education, this paper aims to examine levels of literacy among learners and students in the primary, intersen and senior phases, in the attempt to understand and to address at least some of the issues in the high drop-out and failure rates at tertiary level. The writers suggest that there is no simple solution nor single strategy but that theory and actual practice working together may engender meaningful change. With this aim in mind, 17 stakeholders were interviewed and their responses recorded and carefully analysed.